The utility of meaning : what words mean and why - Enfield, N. J., 1966- (Oxford : Oxford University Press, 2015)
This book argues that the complex, anthropocentric, and often culture-specific meanings of words have been shaped directly by their history of 'utility' for communication in social life. N.J. Enfield draws on semantic and pragmatic case studies from his extensive fieldwork in Laos to investigate a range of semantic fields including emotion terms, culinary terms, landscape terminology, and honorific pronouns, among many others. These studies form the building blocks of a conceptual framework for understanding meaning in language. The book argues that the goals and relevancies of human communication are what bridge the gap between the private representation of language in the mind and its public processes of usage, acquisition, and conventionalization in society. Professor Enfield argues that in order to understand this process, we first need to understand the ways in which linguistic meaning is layered, multiple, anthropocentric, cultural, distributed, and above all, useful. This wide-ranging account brings together several key strands of research across disciplines including semantics, pragmatics, cognitive linguistics, and sociology of language, and provides a rich account of what linguistic meaning is like and why.
Utility of meaning -- Meanings are layered -- Meanings are multiple -- Meanings are anthropocentric -- Meanings are cultural -- Meanings are distributed -- Meanings are useful.
Includes bibliographical references (p. 177-195) and index.
Keywords: Lao language -- Semantics; Meaning (Psychology)